Arilalquilpiperazinas como agentes multialvo moduladores de receptores histaminérgicos, dopaminérgicos e da acetilcolinesterase - Aranha, Cecilia Maria Simoes De Queiroz [UNIFESP] (2021)
Several neurological disorders can be associated with cognitive decline, and the mechanisms responsible for controlling these disorders are complex and diverse. The role of cholinergic, histaminergic and dopaminergic neurotransmission has considerable relevance for the development of these difunctions, and the heterogeneous nature indicates that multi-target strategies, considering targets associated to these systems, may be more appropriate in the treatment of these disfunctions. In this scenario, this work presents a series of 24 arylalkylpiperazines, with different aromatic nuclei (naphthyl, benzofuranyl and quinolinyl), linkers (ethylene and propylene) and substituents in the piperazine terminal nitrogen (methyl, phenyl and pyridyl), synthesized from classic organic reactions, which led to yields varying from 21 to 97%. Out of these, 12 compounds were evaluated at histamine H3 (H3R) and H4 (H4R) and dopamine D2 (D2R) and D3 (D3R) receptors through binding assays, while 21 compounds were evaluated for acetylcholinesterase (AChE) inhibition using a modified Ellman’s method. Seven compounds showed good affinity for H3R, with compound LINS05014 showing the best affinity (1,1 µM), and most showed good selectivity over H4R. Four compounds showed good affinity for D3R, with compound LINS05006 showing the best affinity (0,7 µM), and also showed good selectivity over D2R. The compounds showed low affinity for AChE, with compound LINS05030 showing the best affinity (72,7 µM). As for multitargeting approach, two compounds showed to be promising in the three selected targets (LINS05006 = Ki: H3R = 2.8 µM; D3R = 0.7 µM; IC50: AChE = 107.1 µM; LINS05020 = Ki: H3R = 1.7 µM; D3R = 1.4 µM; IC50: AChE = 114.7µM) and can be used as a prototype, together with overall results, to improve the development of better multitargeting ligands.